POROUS CATALYST LAYER FOR PEM FUEL CELLS BASED ON PLATINIC SALT ACIDS DISPERSED ON HIGH SURFACE AREA CARBON POWDER - Mohamad Y. Mustafa; Mohammad H. Kailani (Research Retrieval and Academic Letters, 2024)
One of the major breakthroughs in the fuel cell science was the significant reductions in Membrane Electrode Assembly’s (MEA) platinum loadings from the high loadings of 5–10 mg /cm2 Pt/C in the early 1990s to less than 1mg/cm2 Pt/C in recent work, a development which was primarily due to the substitution of Pt-black catalysts with higher surface area carbon-supported Pt catalysts, as well as the use of perfluorosulfonic-ionomer binder in thin-film catalyst layers. In this work, a novel approach in the preparation of catalyst material with catalyst loadings of 10 and 30 wt. % Pt/Ca, using a platinum salt as the source of platinum, which is dispersed on carbon particles through an impregnation process is presented. Characterization indicated satisfactory dispersion of platinum particles on the carbon black, and acceptable chemical properties. The prepared catalyst was applied as a solution on both faces of the membrane using a brush method. To overcome application challenges, a catalyst layer was prepared in the form of a thin film away from the membrane and then was placed on both sides of the proton conducting polymer membrane as separate layers, which indicated satisfactory properties and potential for implementation in commercial fuel cells.